Family, work, collegial, and emotional influences on problem-focused voice behaviors - De Clercq, D.; Pereira, R. (Journal of Applied Behavioral Science, 2022)
This study details the unexplored connection between employees’ exposure to family incivility and voice behavior to pinpoint organization problems, considering the mediating role of their work engagement and the moderating role of their emotion sharing with colleagues in this connection. Survey data obtained from employees who work in the banking sector reveal that a critical reason rude treatment by family members keeps employees from expressing their opinions about organizational shortcomings at work is that they exhibit limited positive work energy. This explanatory role of work engagement is less salient though when employees can draw on the relational resource of emotion sharing. For organizational change professionals, this study accordingly showcases a core explanation, thwarted work engagement, by which family-related hardships prevent employees from undertaking productive problem-focused voice activities, and it explicates how this mechanism can be subdued if the work environment encourages employees to express personal feelings openly to their peers.